Recent strategies for drug development in fibromyalgia syndrome. (1st December 2016) - Blumenthal, David E.; Malemud, Charles J.
ABSTRACT: Introduction : The US Federal Drug Administration (FDA) approved 3 medications for treating fibromyalgia syndrome (FMS). There have been no additional FDA approvals since January 2009 and the efficacy of the FDA-approved medications for FMS has been questioned. Areas covered : The "search for studies" tool using clinicaltrials.gov and PubMed were employed. The term, "fibromyalgia" was used for clinicaltrials.gov. The terms employed for PubMed were "Name-of-Drug Fibromyalgia", "Fibromyalgia Treatment" or "Fibromyalgia Drug Treatment." Clinical trials were reviewed if they were prospective and blinded, and if they employed a comparator, either placebo or another pharmaceutical. Expert commentary : Progress toward standardizing the outcome measures for FMS clinical trials have been made but challenges remain. Several pharmaceutical candidates for FMS have been tested since 2009. The results of these studies with potential novel targets for drug development for FMS were reviewed including the results of trials with sodium oxybate, quetiapine, esreboxetine, nabilone, memantine, naltrexone, and melatonin.